Tindak Tutur Ilokusi dalam Film Wang Sinawang Karya Thomas Chris - Ananto, Johan Rinus; Surana, Surana (Jurnal Online Baradha, 2023)
"Wang Sinawang" film by Thomas Chris is a film about literacy. This research direction to explain the variation also forms of illocutionary speech acts, context and purpose of illocutionary speech acts in "Wang Sinawang" film by Thomas Chris. This research uses descriptive qualitative research. Data sources are taken from speech or communication in "Wang Sinawang" film. This film explain through the importance of literacy so that you are not easily deceived. The procedure of gathering data in this research is using documentation, listening, and note-taking techniques. In this study the researcher as a research instrument. The method used in this research is descriptive qualitative method with pragmatic theory. The data is taken from conversations or film dialogues, which contain 9 utterances of illocutionary speech acts. Of the 9 utterances, there are 5 utterances which are included as assertive illocutionary acts. 2 utterances including directive illocutionary speech acts. 2 speech includes expressive illocutionary speech acts. The context of utterances found there were 2 utterances included in the context section. There is 1 utterance that includes contextual context. 1 utterances include actional contexts. The purpose of illocutionary speech acts was found to be 2 utterances included in the type of purpose. There are 1 utterances that include competitive objectives. 1 utterances that include convivial purposes. Keywords: Illocutionary Speech Acts, Types of Illocutionary Speech Acts, Context of Speech, and Purpose of Illocutionary Speech Acts. Film "Wang Sinawang" karya Thomas Chris yaitu film yang berisi tentang literasi. Penelitian ini mempunyai tujuan untuk menjelaskan jenis dan wujud tindak tutur ilokusi, konteks serta tujuwan tindak tutur ilokusi yang ada pada film "wang sinawang" karya Thomas Chris. Kajian ini memakai kajian kualitatif deskriptif. Sumber data diambil dari tuturan maupun intraksi di film "Wang Sinawang". Film ini mengisahkan mengenai pentingnya literasi supaya tidak gampang ditipu. Teknik mengumpulkan data pada kajian ini yaitu memakai metode dokumentasi, menyimak, serta mencatat. Pada kajian ini penulis sebagai instrumen kajian. Teknik yang dipergunakan dalam penelitian ini yaitu teknik deskriptif kualitatif melalui teori pragmatik. Data tersebut diambil dari percakapan atau dialog film, yang mengandung tindak tutur ilokusi yang jumlahnya ada 9 tuturan. Dari 9 tuturan itu ada 5 dialog yang termasuk tindak tutur ilokusi asertif. 2 dialog tergolong tindak tutur ilokusi direktif. 2 dialog tergolong tindak tutur ilokusi ekspresif. Konteks tuturan ditemukan ada 2 tuturan yang termasuk dalam bagian konteks. Ada 1 tuturan yang termasuk konteks kontekstual. 1 tuturan termasuk konteks aksional. Tujuan tindak tutur ilokusi diperoleh ada 2 tuturan yang tergolong pada jenis tujuan. Ada 1 tuturan yang termasuk tujuan kompetitif. 1 tuturan yang termasuk tujuan konvivial. Kata Kunci: Tindak Tutur Ilokusi, Jenis Tindak Tutur Ilokusi, Konteks Tutur, lan Tujuan Tindak Tutur Ilokusi.